Straightforward synthesis of [Cu(NHC)(alkynyl)] and [Cu(NHC)(thiolato)] complexes (NHC = N-heterocyclic carbene). Issue 1 (9th December 2021) - Ibni Hashim, Ishfaq; Scattolin, Thomas; Tzouras, Nikolaos V.; Bourda, Laurens; Van Hecke, Kristof; Ritacco, Ida; Caporaso, Lucia; Cavallo, Luigi; Nolan, Steven P.; Cazin, Catherine S. J.
Abstract : Synthetic access to monomeric copper-alkynyl and copper-thiolato complexes of the type [(NHC)Cu(R)] (R = alkynyl or thiolato) using a weak base approach is reported. Computational studies and reactivity tests are also presented. Abstract : Synthetic access to monomeric copper-alkynyl and copper-thiolato complexes of the type [(NHC)Cu(R)] (R = alkynyl or thiolato) using a weak base approach is reported. All reported reactions proceed under mild conditions in air and in environmentally acceptable solvents. The novel complexes are fully characterized and single crystal X-ray analyses unambiguously establish the atom connectivity in these mononuclear complexes. The importance of the supporting NHC ligand's steric properties in stabilizing mononuclear complexes is discussed.